Delicacies of bassinet and bed: sacrificial birth and wedding banquets in the Athenian democracy in the fourth century BC - Notario Pacheco, Fernando (ARYS. Antigüedad: Religiones y Sociedades, 2020)
While the public sacrifices have been deeply studied in the last years by scholars and specialists in Greek classical culture, the familiar sacrificial feasts haven´t received the same attention. In this contribution, we are going to study one of the most relevant aspects in this kind of celebrations: the acquisition, preparation, exhibition and consumption of food. In doing so, it will be seen how these practices are related with more general processes in the Greek world along the Fourth Century BC, where the food is a key element for thinking, understanding and expressing the interpersonal and social relationships.